Improvement of Photovoltaic Performance of Polymer Solar Cells by Rational Molecular Optimization of Organic Molecule Acceptors. Issue 23 (21st June 2018) - Li, Xiaojun; Yao, Jia; Angunawela, Indunil; Sun, Chenkai; Xue, Lingwei; Liebman‐Pelaez, Alexander; Zhu, Chenhui; Yang, Chunhe; Zhang, Zhi‐Guo; Ade, Harald; Li, Yongfang
Abstract: Two n‐type organic semiconductor (n‐OS) small molecules m ‐ITIC‐2F and m ‐ITIC‐4F with fluorinated 2‐(2, 3‐dihydro‐3‐oxo‐1H‐inden‐1‐ylidene)propanedinitrile (IC) terminal moieties are prepared, for the application as an acceptor in polymer solar cells (PSCs), to further improve the photovoltaic performance of the n‐OS acceptor 3, 9‐bis(2‐methylene‐(3‐(1, 1‐dicyanomethylene) indanone) ‐5, 5, 11, 11‐tetrakis(3‐hexylphenyl)‐dithieno[2, 3‐d:2′, 3′‐d′]‐sindaceno[1, 2‐b:5, 6‐b′]‐dithiophene ( m ‐ITIC). Compared to m ‐ITIC, these two new acceptors show redshifted absorption, higher molecular packing order, and improved electron mobilities. The power conversion efficiencies (PCE) of the as‐cast PSCs with m ‐ITIC‐2F or m ‐ITIC‐4F as an acceptor and a low‐cost donor–acceptor (D–A) copolymer PTQ10 as a donor reach 11.57% and 11.64%, respectively, which are among the highest efficiency for the as‐cast PSCs so far. Furthermore, after thermal annealing treatment, improved molecular packing and enhanced phase separation are observed, and the higher PCE of 12.53% is achieved for both PSCs based on the two acceptors. The respective and unique advantage with the intrinsic high degree of order, molecular packing, and electron mobilities of these two acceptors will be suitable to match with different p‐type organic semiconductor donors for higher PCE values, which provide a great potential for the PSCs commercialization in the near future. These results indicate that rational molecular structure optimization is of great importance to further improve photovoltaic properties of the photovoltaic materials. Abstract : Two n‐type organic semiconductor (n‐OS) molecules m ‐ITIC‐2F and m ‐ITIC‐4F are prepared, which are fluorine‐substituted compounds on the end groups of m ‐ITIC. The new n‐OS molecules exhibit enhanced long‐wavelength absorption, higher molecular packing order, and improved electron mobilities. The two new acceptor‐based polymer solar cells (PSCs) with PTQ10 as a donor both achieved high power conversion efficiency of 12.53%.